EFECTO DE LAS TASAS DE INTERÉS Y LA MASA MONETARIA EN EL ÍNDICE DE INFLACIÓN DE ECUADOR, EN EL PERIODO 1960 – 2015. - López Mogrovejo, Daniela Nathaly (2019)
For a long time the Ecuador has been suffering from very fluctuating inflation processes, bringing many times the economic instability as a consequence. The most relevant factors to predict the inflation are the interest rates and the money supply. Therefore, the purpose of the follow investigation is to analyze the effect of these variables on the inflation in Ecuador during the period of 1960 to 2015. For the development, annual data of the World Development Indicators from the World Bank of the aforementioned years were used. Time series methodology were also used, taking as dependent variable the inflation measured as a percentage of the consumer price index and as independent variables the interest rate as the real interest rate and money supply as the money supply at current prices and a dichotomous variable that encompasses the dollarization process. The main result found agrees with Taylor’s rule and shows that in Ecuador the interest rate is statistically significant, that is, directly affects the inflation of the country when it’s taken into account with the money supply.